PENGARUH IKLIM ORGANISASI DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Pada Tenaga Medis Rumah Sakit Ibu dan Anak Annnisa Pekanbaru) - Lia Maharani (Politeknik Bisnis Indonesia, 2023)
This study aims to determine and analyze the influence of organizational climate, organizational culture on organizational citizenship behavior in medical personnel of Annisa Pekanbaru Mother and Child Hospital. The research method used is quantitative research method. This study used the census method on a sample of 55 responses because the total respondents were less than 100, so all of them were used as samples. The tests conducted in this study consisted of validity tests, reality tests, classical assumption tests, data analysis tests, hypothesis tests and determination coefficient tests, all of which were carried out with the Social Statistics Package of the Computer Sciences Program (SPSS) version 25.0. The results of the tests conducted show that organizational climate has a positive and significant influence on organizational citizenship behavior, organizational culture has a positive and significant influence on organizational citizenship behavior and organizational climate and organizational culture has a positive and significant influence on organizational citizenship behavior.